Solar photovoltaic assisted cost-efficient brackish water purification system - Kabir K.M.; Matin M.A.; Misran H.; Amin N. (Institute of Electrical and Electronics Engineers Inc., 2023)
Cost benefit analysis; Desalination; Developing countries; Purification; Renewable energy resources; Reverse osmosis; Rural areas; Solar concentrators; Solar power generation; Water resources; Water treatment plants; Brackish water; Brackish water reverse osmosis; Experimental investigations; International standards; Renewable energies; Small scale power generation; Solar PVs; Water purification systems; Potable water